Micronutrient specific SSR marker based diversity analysis for developing short duration wheat (Triticum aestivum) - PHOUGAT, DIVYA; SETHI, S K (The Indian Journal of Agricultural Sciences, 2020)
Malnutrition leads to high mortality especially in developing countries. Present study comprised 11 high yielding wheat (Triticum aestivum L.) genotypes sown during rabi 2014-15 and 2015-16 and crosses attempted during 2014-15 and sown at Research Field of CCS Haryana Agricultural University, Hisar, Haryana. Forty nine microsatellite markers linked with identified QTLs for micronutrient were used for the genetic diversity assessment among bread wheat parents their F1s. Out of 49, 38 SSRs were found polymorphic which amplified a total of 76 alleles with an average of 2.00 alleles per locus. The range of amplified PCR products ranged from 100 to 480 bp. Estimates of similarity coefficient among parents and F1s suggest enough divergence and averaged to 0.71. Enough genetic variability was observed for all the 14 agronomic traits in all genotypes. Selection of genotypes from different clusters helps in making proper choice of breeding programme. In the present study, the information generated about genetic diversity will be useful for selection of parents for breeding including gene mapping and ultimately for marker assisted selection (MAS) for micronutrient content improvement worldwide.